Patterned conductive liquid metal composite film and preparation method and application thereof
Through organic matter-assisted and mechanical activation methods, the problem of liquid metal forming film on the substrate is solved, high-precision patterning is achieved, electrical conductivity and flexibility are improved, and the application range is expanded to meet the high-performance needs of flexible electronic devices.
Patent Information
- Application Number
- CN202510394781.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-07-04
AI Technical Summary
In the prior art, liquid metals are difficult to form a continuous film on the substrate, and have low patterning accuracy, difficult to take into account both conductivity and flexibility, and poor environmental stability, which limits its application in flexible electronic devices.
Through the interaction of organic matter and the surface oxide layer of liquid metal micro-nanoparticles, combined with spin coating, scraping or inkjet printing processes, a conductive liquid metal composite film is formed, and high-precision patterning is achieved through mechanical activation and laser ablation.
It significantly improves the dispersion and film formation of liquid metals, forms a uniform film, enhances conductivity and flexibility, expands the scope of application, and meets the high-precision needs in the fields of flexible displays, wearable devices and biosensors.
Smart Images

Figure CN120261021A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of flexible electronic technology, and mainly to a patterned conductive liquid metal composite film and a preparation method and application thereof. Background Art
[0002] Flexible electronic devices have attracted much attention due to their huge application potential in wearable devices, flexible displays, biomedical sensors and other fields. Compared with traditional rigid electronic devices, flexible electronic devices are bendable and stretchable, and can better adapt to various complex application scenarios, bringing new opportunities for the development of electronic technology. However, the development of flexible electronic devices faces many challenges, the most critical of which is the selection and manufacturing process of flexible conductive materials.
[0003] Although traditional metal films (such as silver and copper) have excellent conductivity, their rigidity and brittleness limit their application in flexible electronic devices. Although metal nanomaterials and carbon-based materials (such as carbon nanotubes and graphene) have certain flexibility, they have problems such as poor adhesion, unstable conductivity, and difficulty in achieving high-precision patterning. Liquid metal, as an emerging conductive material, has attracted much attention due to its unique high conductivity and fluidity. However, the high surface tension of liquid metal makes it difficult to wet most substrate materials to form a film, limiting its application in the field of optoelectronic functional thin film devices.
[0004] In order to solve these problems, researchers are committed to developing new flexible conductive materials and their preparation processes. In recent years, the application of liquid metal in flexible electronic devices has gradually become a research hotspot through methods such as organic assistance, surface modification, and composite material design. These methods not only improve the film-forming and patterning capabilities of liquid metals, but also enhance their stability in complex environments. However, the existing technology still has many shortcomings, such as low patterning accuracy, difficulty in balancing conductivity and flexibility, and poor environmental stability. Therefore, the development of an efficient, stable and flexible conductive material suitable for a variety of substrates and its preparation process is of great significance to promote the development of flexible electronic devices. Summary of the invention
[0005] In view of the problems existing in the prior art, the present application proposes a patterned conductive liquid metal composite film and a preparation method thereof.
[0006] According to one aspect of the present invention, a conductive liquid metal composite film is proposed, comprising liquid metal micro-nanoparticles and organic matter; the organic matter can interact with the surface oxide layer of the liquid metal micro-nanoparticles, and the interaction includes hydrogen bonds and van der Waals forces; the conductive liquid metal composite film is formed on a film-forming substrate by spin coating, blade coating or inkjet printing and by mechanical activation.
[0007] Through the interaction between the organic matter and the surface oxide layer of the liquid metal micro-nano particles, the dispersibility and film-forming property of the liquid metal are significantly improved, effectively solving the problem that it is difficult for the liquid metal to form a film on the substrate due to its high surface tension. Through spin coating, blade coating or inkjet printing processes, this solution realizes the efficient deposition of the liquid metal composite material, further improving the flexibility and adhesion of the film, enabling the liquid metal composite material to form a uniform film on various flexible and rigid substrates. At the same time, mechanical activation ensures the formation of a conductive path, endowing the film with excellent electrical conductivity. In addition, this solution can achieve high-precision patterning of the conductive liquid metal composite film through laser ablation, and can fabricate complex circuit and electrode structures to meet the high-precision requirements in fields such as flexible displays, wearable devices and biosensors.
[0008] Preferably, the liquid metal micro-nano particles include gallium-indium alloy or gallium-indium-tin alloy, and the gallium-indium alloy or the gallium-indium-tin alloy can be doped with one or more metal elements, and the metal elements include gold, silver, copper and iron.
[0009] In a specific embodiment, doping metal elements in the gallium-indium alloy or gallium-indium-tin alloy can reduce its surface tension, making it easier to form a uniform film on the substrate; at the same time, it can further increase the electrical conductivity of the liquid metal, and a more efficient conductive network can be formed after doping.
[0010] Preferably, the organic matter includes organic macromolecules or organic polymers, and the organic macromolecules or organic polymers contain groups with lone pair electrons of oxygen atoms or lone pair electrons of nitrogen atoms, and the groups include one or more of hydroxyl, amino, carboxyl and sulfonic acid groups.
[0011] In a specific embodiment, the organic matter is dissolved in the corresponding liquid solvent to form an organic solution. Relying on the abundant functional groups in the solution, the organic matter can interact with the surface oxide layer of the liquid metal micro-nano particles to form hydrogen bonds or van der Waals forces. This interaction can effectively prevent particle aggregation, improve the dispersibility of the liquid metal micro-nano particles in the solution, and thus prepare a uniform and stable composite material; at the same time, the addition of the organic matter also enhances the wettability between the liquid metal and the substrate, enabling it to form a film on various different types of substrates. In addition, with the assistance of the organic matter, the liquid metal micro-nano particles can break through the surface oxide layer through mechanical activation after film formation, and then form a continuous conductive path to achieve excellent electrical conductivity of the film.
[0012] According to the second aspect of the present invention, a method for preparing a conductive liquid metal composite film is proposed, including the following steps:
[0013] S1. Prepare the liquid metal micro-nano particles and the organic solution;
[0014] S2. Mix the liquid metal micro-nano particles and the organic solution to obtain a liquid metal composite material;
[0015] S3. Spin coat, blade coat or inkjet print the liquid metal composite material on a film-forming substrate to form a liquid metal composite film;
[0016] S4. Mechanically activate the liquid metal composite film to form continuous conductive paths, thereby obtaining the conductive liquid metal composite film.
[0017] This method cleverly solves the problem of liquid metal film formation through organic matter assistance and mechanical activation, and realizes high-precision patterning while simplifying the process flow. First, the interaction between the organic matter and the surface oxide layer of the liquid metal reduces the surface tension of the liquid metal, significantly improving its dispersibility and film-forming property on various substrates, providing a solid foundation for subsequent patterning treatment and creating favorable conditions for achieving high-precision patterning. After film formation, the mechanical activation step is used to break the oxide layer on the surface of the liquid metal, promote particle fusion, and form continuous conductive paths, realizing excellent electrical conductivity of the film. This process not only simplifies the preparation process, reduces costs, but also expands the application range of liquid metal composite films in flexible electronic devices, providing high-performance conductive material solutions for fields such as flexible display control devices, wearable devices, and biosensors, especially showing significant advantages in balancing process simplicity and patterning accuracy.
[0018] Preferably, the concentration of the organic solution is 1 mg / ml - 10 g / ml.
[0019] In a specific embodiment, a low-concentration organic solution can ensure good dispersibility of the liquid metal micro-nano particles in the solution; while an overly high-concentration organic solution may cause the liquid metal particles to be overly wrapped, increasing the possibility of particle agglomeration and reducing the dispersion effect. This concentration design can not only provide sufficient functional groups to interact with the surface oxide layer of the liquid metal, but also avoid particle agglomeration, thereby achieving uniform dispersion, enabling the liquid metal composite material to form a uniform film during spin coating, blade coating or inkjet printing.
[0020] Preferably, the volume ratio of the liquid metal micro-nano particles to the organic solution is 4:1 - 1:4.
[0021] In specific embodiments, when the volume ratio is low (less liquid metal), the composite material has better flexibility, adhesion, and environmental stability, but the conductivity may decrease slightly; when the volume ratio is high (more liquid metal), the conductivity of the composite material is significantly improved, but the flexibility and adhesion may be affected to a certain extent, and the environmental sensitivity increases. Therefore, selecting an appropriate volume ratio requires a trade-off based on specific application scenarios and performance requirements. In this solution, the volume ratio is limited to the range of 4:1 to 1:4, which can better balance these properties and achieve the best balance among conductivity, flexibility, and environmental stability.
[0022] Preferably, the film-forming substrate includes a silicon wafer, glass, stainless steel, polydimethylsiloxane (PDMS), polystyrene block copolymer (SEBS), or a commercial transparent tape.
[0023] Based on the special material formula and preparation process of this solution, the conductive liquid metal composite film of this solution can realize the processing and film formation of liquid metal on various substrates. In specific embodiments, selecting different film-forming substrates can enable the film to be applied to different scenarios. Silicon wafers or glass have high flatness, good chemical stability, and thermal stability, and are suitable for application scenarios with requirements for optical performance and thermal management; while PDMS and SEBS, due to their excellent flexibility and biocompatibility, become ideal choices for flexible electronic devices and biomedical applications; stainless steel, with its high strength, corrosion resistance, and good thermal conductivity, is suitable for scenarios that require high mechanical strength and adaptability to harsh environments. The rich and diverse substrate selection provides broad application prospects for the conductive liquid metal composite film, enabling it to meet the needs of multiple fields from high-performance electronic devices to flexible wearable devices and biomedical sensors, fully demonstrating its strong adaptability and application potential in modern electronic technology.
[0024] Preferably, in S4, the mechanical activation includes pressing the liquid metal composite film with a metal rod or a roller to break the surface oxide film of the liquid metal composite film to form a continuous conductive path.
[0025] In specific embodiments, pressing with a metal rod or a roller can effectively break the surface oxide film of the liquid metal composite film, making the liquid metal particles contact and fuse with each other to form a continuous conductive network; in addition, after the conductive liquid metal composite film is damaged, the damaged area can be reactivated by mechanical activation to restore the conductive ability again.
[0026] According to the third aspect of the present invention, a flexible display control device is proposed, including a flexible circuit made of a conductive liquid metal composite film.
[0027] In a specific embodiment, the conductive liquid metal composite film can be used to fabricate flexible circuits and encapsulation layers of flexible display control devices (such as flexible light-emitting diode display screens). With its excellent conductivity and flexibility, the conductive liquid metal composite film can not only efficiently meet the requirements of high current density and fast signal transmission, but also maintain stable conductive performance under complex mechanical deformations, demonstrating extremely high stability. In addition, the preparation process of this film is simple, the cost is low, and it has good compatibility with a variety of substrate materials. These characteristics together significantly improve the overall performance and reliability of flexible display control devices.
[0028] Preferably, the conductive liquid metal composite film forms a pattern or array structure through laser ablation.
[0029] Through laser ablation, the conductive liquid metal composite film can achieve high-precision patterning to form high-precision patterns and array structures, including circuits and electrodes, etc. The ablated area can absorb the functional laser and generate gasification, completely losing its conductivity, while the remaining area still maintains high conductivity, ensuring the stability and functionality of the circuit. This high-precision patterning ability meets the requirements for complex circuit and electrode structures in fields such as flexible displays, wearable devices, and biosensors. At the same time, as a non-contact processing method, laser ablation can reduce damage to the substrate and improve the overall quality and reliability of the film.
[0030] Compared with the prior art, the present application has the following beneficial effects:
[0031] (1) In the present application, by using an organic substance to assist liquid metal, a solution processing method for film formation is realized, which greatly improves the dispersibility and film-forming property of liquid metal, overcoming the problem that traditional liquid metal is difficult to form a continuous film due to mismatched surface energy; in addition, this method can realize solution processing and film formation of liquid metal on a variety of substrate materials, greatly expanding its application range;
[0032] (2) After mechanical activation, the conductive liquid metal composite film of the present application can form continuous conductive channels, significantly improving the conductive performance of the film; in addition, even in damaged areas, the conductivity can be restored by reactivation, greatly improving the reliability and service life of the material;
[0033] (3) The conductive liquid metal composite film of the present application can achieve high-precision patterning through laser ablation, and can accurately prepare complex circuit and electrode structures. This characteristic meets the requirements for high-precision patterning in fields such as flexible displays, wearable devices, and biosensors, providing strong support for the development of high-performance flexible electronic devices;
[0034] (4) Through the method of the present application, flexible, stretchable and patterned electrodes and circuits can be efficiently prepared, fully meeting the preparation requirements of optoelectronic devices. This process is not only simple and easy to implement, but also very suitable for large-scale production, demonstrating great commercial potential and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The accompanying drawings are included to provide a further understanding of the embodiments and are incorporated into and constitute a part of this specification. The drawings illustrate the embodiments and, together with the description, are used to explain the principles of the present application. Other embodiments and many of the expected advantages of the embodiments will be readily apparent as they become better understood by reference to the following detailed description. The elements of the drawings are not necessarily to scale relative to each other. Like reference numerals refer to corresponding like parts.
[0036] Figure 1 FIG. shows a schematic preparation process flow of a conductive liquid metal composite film according to an embodiment of the present application;
[0037] Figure 2 FIG. shows a physical diagram of a liquid metal composite film according to a specific embodiment of the present application;
[0038] Figure 3 FIG. shows a physical diagram of a conductive liquid metal composite film according to a specific embodiment of the present application;
[0039] Figure 4 FIG. shows a voltage-current test curve of a conductive liquid metal composite film after mechanical activation according to a specific embodiment of the present application;
[0040] Figure 5 FIG. shows a physical diagram of a patterned conductive liquid metal composite film according to another specific embodiment of the present application;
[0041] Figure 6 FIG. shows a voltage-current test curve of a conductive liquid metal composite film after mechanical activation according to another specific embodiment of the present application. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0042] The present application will be further described in detail below with reference to the accompanying drawings and embodiments. It can be understood that the specific embodiments described herein are only for explaining the related invention and not for limiting the invention. Additionally, it should be noted that for the sake of description, only parts related to the relevant invention are shown in the drawings. Without conflict, the embodiments in the present application and the features in the embodiments can be combined with each other. The present application will be described in detail below with reference to the drawings and in conjunction with the embodiments.
[0043] Figure 1 is a schematic preparation process flow diagram of the conductive liquid metal composite film of the present invention. Refer toFigure 1 , the specific preparation process is as follows:
[0044] S1. Prepare liquid metal micro-nano particles and an organic solution;
[0045] S101. Put liquid metal and an ethanol solution into a container, and perform ultrasonic dispersion treatment under an ice-water bath condition. After the ultrasonic treatment ends, let it stand for a period of time. After standing and sedimentation, remove the supernatant to obtain liquid metal micro-nano particles;
[0046] S102. Dissolve the organic matter in the corresponding solvent to obtain an organic solution;
[0047] S2. Mix the liquid metal micro-nano particles and the organic solution to obtain a liquid metal composite material;
[0048] S3. Spin coat, knife coat or inkjet print the liquid metal composite material on a film-forming substrate to form a liquid metal composite film;
[0049] S4. Mechanically activate the liquid metal composite film to form continuous conductive paths, and obtain a conductive liquid metal composite film.
[0050] In a specific embodiment, the organic matter includes polyacrylic acid, polyacrylamide, polyvinyl alcohol, polyaniline, polyethyleneimine, polyvinylpyrrolidone, polyvinylidene fluoride, tannic acid, hyaluronic acid or a conductive polymer; the solvent includes deionized water, ethanol, isopropanol, toluene or dimethyl sulfoxide.
[0051] Example 1
[0052] A conductive liquid metal composite film, and its specific preparation steps are as follows:
[0053] A1. Prepare liquid metal micro-nano particles and an organic solution;
[0054] A101. Take 0.5 g of gallium-indium alloy and 5 mL of ethanol solution and put them into a reagent bottle. Use a BILON-650Y ultrasonic cell disruptor to perform ultrasonic treatment under an ice-water bath condition. The ultrasonic power is 195 W, stop for 5 s every 5 s of operation, and keep it for 20 min; after the ultrasonic treatment ends, let the reagent bottle stand. After standing and sedimentation, remove the supernatant to obtain liquid metal micro-nano particles;
[0055] A102. Take 90 mg of polyvinyl alcohol (PVA) and 3 mL of deionized water and place them in a new reagent bottle. Slowly heat it to 90 °C under stirring at 300 rpm until the PVA is completely dissolved to obtain a 30 mg / mL PVA aqueous solution;
[0056] A2. Take 300 μL of liquid metal micro-nano particles and 150 μL of 30 mg / mL PVA aqueous solution in a small reagent bottle, and mix them with a vortex mixer for 2 min to obtain a liquid metal composite material;
[0057] A3. Prepare a liquid metal composite film;
[0058] A301. Take 3 mL of polydimethylsiloxane (PDMS) base solution and 0.3 mL of curing agent, mix them, stir with an aluminum rod for 1 min, then use a vacuum drying oven to remove air bubbles, and then spin-coat on a glass substrate at 800 rpm for 30 s to prepare a PDMS film. Cure the prepared PDMS film at 70 °C for 2 h;
[0059] A302. After plasma treating the PDMS film for 1 min, spin-coat the liquid metal composite material onto the PDMS film to obtain a liquid metal composite film, as Figure 2 shown. The spin-coating speed is 500 rpm, and the spin-coating time is 1 min;
[0060] A4. Press and mechanically activate the liquid metal composite film with a roller to obtain a conductive liquid metal composite film, as Figure 3 shown.
[0061] Figure 4 is the voltage-current test curve of the conductive liquid metal composite film after mechanical activation. It can be observed from the figure that the film exhibits excellent linear conductive characteristics, which is a strong proof of high conductivity. Specifically, within a relatively small voltage change range, the film generates a significant current response, indicating that the film has a low resistance value, which is conducive to the efficient transmission and conversion of electrical energy. In addition, the stable linear relationship presented in the figure further confirms the effectiveness of the mechanical activation process in improving the conductive performance of the film. Through mechanical activation, the liquid metal particles are rearranged to form a more continuous and compact conductive path, thereby significantly reducing the resistance of the film and enhancing its conductive ability. This process not only optimizes the electrical properties of the film but also provides a solid foundation for its application in flexible electronic devices.
[0062] Figure 5 shows the conductive liquid metal composite film after laser ablation treatment, which forms a precisely controlled special pattern. This result clearly indicates that the conductive liquid metal composite film prepared by this scheme has excellent high-precision patterning ability; the application of laser ablation technology makes the patterning process of the film more precise and controllable, enabling highly complex circuit designs and electrode layouts. In addition, the film prepared by this scheme can still maintain excellent conductivity and mechanical stability after laser ablation, which is a great advantage for ensuring the performance and reliability of the device.
[0063] Example 2
[0064] A conductive liquid metal composite film, and its specific preparation steps are as follows:
[0065] B1. Prepare liquid metal micro-nano particles and an organic solution;
[0066] B101. Take 0.5 g of gallium-indium alloy and 5 mL of ethanol solution and put them into a reagent bottle. Under the condition of ice-water bath, use a BILON-650Y ultrasonic cell disruptor for ultrasonic treatment. The ultrasonic power is 195 W, stop for 5 s every 5 s of operation, and keep for 20 min; after the ultrasonic treatment, let the reagent bottle stand still. After standing and sedimentation, remove the supernatant to obtain liquid metal micro-nano particles;
[0067] B102. Take 100 mg of polyvinylpyrrolidone (PVP) and 2 mL of ethanol and place them in a new reagent bottle. Under the condition of ice-water bath, use a WM-300DE ultrasonic cleaner for ultrasonic treatment for 30 min. The ultrasonic power is 300 W to obtain a 50 mg / mL PVP aqueous solution;
[0068] B2. Take 300 μL of liquid metal micro-nano particles and 150 μL of 50 mg / mL PVP aqueous solution in a small reagent bottle, and use a vortex mixer to mix for 2 min to obtain a liquid metal composite material;
[0069] B3. Use a glass slide as a film-forming substrate. After plasma treatment of the glass slide for 1 min, spin-coat the liquid metal composite material onto the glass slide to obtain a liquid metal composite film. The spin-coating speed is 500 rpm and the spin-coating time is 1 min;
[0070] B4. Use a roller to press and mechanically activate the liquid metal composite film to obtain a conductive liquid metal composite film.
[0071] Figure 6 This is the voltage-current test curve after mechanical activation of the conductive liquid metal composite film. It can be observed from the figure that the film also exhibits excellent linear conductive characteristics and has high conductivity.
[0072] The above results show that the conductive liquid metal composite film of the present invention has excellent linear conductive characteristics and can efficiently transmit and convert electrical energy. In addition, the film can form a uniform film layer on a variety of different substrate materials and maintain excellent conductivity and stable linear characteristics. This result indicates that the present solution has universality and can successfully realize the film formation of liquid metal on diverse substrates. At the same time, the consistent performance test results further verify the high repeatability of the present solution, which means that the solution can reliably and stably mass-produce conductive liquid metal composite films with consistent performance, showing great potential and value in practical applications.
[0073] The specific embodiments of the present application have been described above. However, the protection scope of the present application is not limited thereto. Any person skilled in the art within the technical scope disclosed by the present application can easily think of changes or substitutions, which should all be covered within the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the protection scope of the claims.
[0074] In the description of the present application, it should be understood that the orientation or positional relationship indicated by the terms "upper", "lower", "inner", "outer", etc. is based on the orientation or positional relationship shown in the drawings. It is only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, it should not be construed as a limitation to the present application. The word 'comprising' does not exclude the presence of elements or steps not listed in the claims. The word 'a' or 'an' preceding an element does not exclude the presence of a plurality of such elements. The simple fact that certain measures are recited in mutually different dependent claims does not indicate that a combination of these measures cannot be used to advantage. Any reference signs in the claims should not be construed as limiting the scope.
Claims
1. A conductive liquid metal composite film, characterized in that, It includes liquid metal micro-nano particles and organic substances; the organic substances can interact with the surface oxide layer of the liquid metal micro-nano particles, and the interactions include hydrogen bonds and van der Waals forces; the conductive liquid metal composite film is formed by spin coating, blade coating or inkjet printing on a film-forming substrate and then mechanically activated.
2. The conductive liquid metal composite film according to claim 1, wherein The liquid metal micro-nano particles include gallium-indium alloy or gallium-indium-tin alloy, and the gallium-indium alloy or the gallium-indium-tin alloy can be doped with one or more metal elements, and the metal elements include gold, silver, copper and iron.
3. The conductive liquid metal composite film according to claim 1, wherein The organic substances include organic macromolecules or polymers, and the organic macromolecules or polymers contain groups with lone pair electrons of oxygen atoms or lone pair electrons of nitrogen atoms, and the groups include one or more of hydroxyl groups, amino groups, carboxyl groups and sulfonic acids.
4. A method for preparing a conductive liquid metal composite thin film according to any one of claims 1-3, characterized in that, It includes the following steps: S1. Prepare the liquid metal micro-nano particles and the organic solution; S2. Mix the liquid metal micro-nano particles and the organic solution, and obtain a liquid metal composite material after ultrasonic stirring; S3. Spin coat, blade coat or inkjet print the liquid metal composite material on a film-forming substrate to form a liquid metal composite film; S4. Mechanically activate the liquid metal composite film to form a continuous conductive path, and obtain the conductive liquid metal composite film.
5. The preparation method of the conductive liquid metal composite film according to claim 4, wherein The concentration of the organic solution is 1 mg / ml - 10 g / ml.
6. The preparation method of the conductive liquid metal composite film according to claim 4, characterized in that The volume ratio of the liquid metal micro-nano particles to the organic solution is 4:1 - 1:
4.
7. The preparation method of the conductive liquid metal composite film according to claim 4, wherein The film-forming substrate includes a silicon wafer, glass, stainless steel, polydimethylsiloxane, polystyrene block copolymer or commercial transparent tape.
8. The preparation method of the conductive liquid metal composite film according to claim 4, wherein, In S4, the mechanical activation includes pressing the liquid metal composite film with a metal rod or a roller to break the surface oxide film of the liquid metal composite film to form a continuous conductive path.
9. A flexible display control device, characterized in that, It includes a flexible circuit made of the conductive liquid metal composite film as described in any one of claims 1 - 3.
10. A flexible display control device according to claim 9, characterized in that, The conductive liquid metal composite film forms a pattern or an array structure by laser ablation.
Citation Information
Cited By
Stretchable transparent electrode based on flexible welding and preparation method thereof
CN120933077A